Flaviata longa, a new species in Flaviata Lu & Qin and new synonymies in Empoasca (Matsumurasca) Anufriev (Hemiptera: Cicadellidae: Empoascini) - Xu, Ye; Lu, Si-Han; Qin, Dao-Zheng (Zootaxa, 2015)
A new species of genus Flaviata Lu & Qin, Flaviata longa sp. nov. is described from Yunnan (southwest China). An identification key for males of all known species in this genus is provided. Photographs and illustrations of adults and male genitalia of the new species are also given. New synonymies for two species in the leafhopper subgenus Empoasca (Matsumurasca) Anufriev of Empoascini are proposed: E. (M.) southerni Zhang, 2014 = E. (M.) clypealata Qin & Zhang, 2011; E. (M.) qini Zhang, 2014 = E. (M.) quadrialata Qin & Zhang, 2011.